A tetraquark or not a tetraquark? A holography inspired stringy hadron (HISH) perspective - Jacob Sonnenschein; Dorin Weissman (Nuclear Physics B, 2017)
We suggest to use the state Y(4630), which decays predominantly to ΛcΛ‾c, as a window to the landscape of tetraquarks. We propose a simple criterion to decide whether a state is a stringy exotic hadron – a tetraquark – or a “molecule”. If it is the former it should be on a (modified) Regge trajectory. We present the predictions of the mass and width of the higher excited states on the Y(4630) trajectory. We argue that there should exist an analogous Yb state that decays to ΛbΛ‾b and describe its trajectory. We conjecture also a similar trajectory for tetraquarks containing strange quarks, and the modified Regge trajectories can in fact be predicted for any resonances found decaying to a baryon–antibaryon pair. En route to the results regarding tetraquarks, we also make some additional predictions on higher excited charmonium states. We briefly discuss the zoo of exotic stringy hadrons and in particular we sketch all the possibilities of tetraquark states.